2019
DOI: 10.3390/medicina55090519
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Exopolysaccharides Produced by Lactic Acid Bacteria of the Genera Pediococcus, Leuconostoc and Lactobacillus against Human Adenovirus Type 5

Abstract: Background and objectives: The use of antagonistic probiotic microorganisms and their byproducts represents a promising approach for the treatment of viral diseases. In the current work, the effect of exopolysaccharides (EPSs) produced by lactic acid bacteria from different genera on the structural and functional characteristics of cells and the development of adenoviral infection in vitro was studied. Materials and Methods: Cytotoxicity of six EPSs of lactic acid bacteria of the genera Lactobacillus, Leuconos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 27 publications
0
49
0
1
Order By: Relevance
“…Stimulation of innate immune responses by probiotics could be one of the mechanisms responsible for the protection provided by probiotics against viral infection. Other proposed mechanisms include inhibition of virus adsorption and penetration into cells as a result of direct interaction of probiotics and virus, competition between probiotics and virus for epithelial cell receptors, and secretion of metabolites with antiviral activity (Mousavi et al, 2018;Biliavska et al, 2019). Previous studies have shown that specific probiotic bacteria bind to and inactivate rotaviruses and vesicular stomatitis viruses, which lead to blocking of the virus adsorption on the cell (Salminen et al, 2010;Kanauchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of innate immune responses by probiotics could be one of the mechanisms responsible for the protection provided by probiotics against viral infection. Other proposed mechanisms include inhibition of virus adsorption and penetration into cells as a result of direct interaction of probiotics and virus, competition between probiotics and virus for epithelial cell receptors, and secretion of metabolites with antiviral activity (Mousavi et al, 2018;Biliavska et al, 2019). Previous studies have shown that specific probiotic bacteria bind to and inactivate rotaviruses and vesicular stomatitis viruses, which lead to blocking of the virus adsorption on the cell (Salminen et al, 2010;Kanauchi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…An inhibiting mechanism involving a direct interaction between bacterial cell wall components and herpes simplex virus type 2 has been also suggested for Lactobacillus brevis CD2 strain [ 62 ]. Furthermore, exopolysaccharides from Lactobacillus species were demonstrated to completely suppress the production of adenovirus-5 in vitro [ 63 ].…”
Section: Probioticsmentioning
confidence: 99%
“…Lactobacilli, as well as other probiotics, have been reported to possess an immunomodulatory ability and protect from virus infections by enhancing cytokine antiviral responses in respiratory and immune cells and in the intestinal mucosa [ 63 , 64 , 65 , 66 , 67 ]. Oral administration of L. brevis in mice protected the animals from influenza infection through the enhancement of antiviral IFN-α as well as an augmented production of specific-IgA antibodies against the virus [ 68 ].…”
Section: Probioticsmentioning
confidence: 99%
“…Representatives of exopolysaccharides (EPS) producing strains of the genera Streptococcus , Lactococcus , Lactobacillus , Leuconostoc , Pediococcus , and Weissella have been well studied for immunostimulating properties. The EPSs extracted from lactic acid bacteria of the genera Pediococcus , Leuconostoc , and Lactobacillus significantly proved to produce anti-adenovirus effects in cell line studies ( Biliavska et al, 2019 ). Other microbial metabolites like spongouridine, spongothymidine, statins, myriocin, NA255, and cyclosporine were reported to have antiviral activities against HSV1,2, HBV, HIV, influenza virus, HCV, and coronaviruses ( Nkongolo et al, 2014 ).…”
Section: Antivirals From Natural Sourcesmentioning
confidence: 99%